Clinico‐molecular analysis of eleven patients with Hermansky–Pudlak type 5 syndrome, a mild form of HPS. (20th October 2017) - Michaud, Vincent; Lasseaux, Eulalie; Plaisant, Claudio; Verloes, Alain; Perdomo‐Trujillo, Yaumara; Hamel, Christian; Elcioglu, Nursel H.; Leroy, Bart; Kaplan, Josseline; Jouk, Pierre‐Simon; Lacombe, Didier; Fergelot, Patricia; et al.
Summary: Hermansky–Pudlak syndrome (HPS), first described in 1959, is a rare form of syndromic oculocutaneous albinism associated with bleeding diathesis and in some cases pulmonary fibrosis and granulomatous colitis. All 10 HPS types are caused by defects in vesicle trafficking of lysosome‐related organelles (LRO) proteins. The HPS5 protein associates with HPS3 and HPS6 to form the biogenesis of lysosome‐related organelles complex‐2 (BLOC‐2). Here, we report the clinical and genetic data of 11 patients with HPS‐5 analyzed in our laboratory. We report 11 new pathogenic variants. The 11 patients present with ocular features that are typical for albinism, with mild hypopigmentation, and with no other major complication, apart from a tendency to bleed. HPS‐5 therefore appears as a mild form of HPS, which is often clinically undistinguishable from mild oculocutaneous or ocular forms of albinism. Molecular analysis is therefore required to establish the diagnosis of this mild HPS form, which has consequences in terms of prognosis and of clinical management of the patients.